Defect- modulated C, N- ZnO doped ZnS synthesis via self-sacrificial template strategy: A multifunctional platform for environmental applications, and mathematical ecotoxicity profiling evaluation - Simranjit Kaur; Nidhi; Simranjeet Kaur; Deepeka; Shubham Pathak; Sandeep Bansal; Paramdeep Kaur; Sonal Singhal (Journal of Environmental Chemical Engineering, 2026)

Repurposing Coriandrum sativum L. powder into bifunctional graphene oxide decorated biochar material for efficient removal of emerging pollutants and sensing of uranyl ions - Nidhi; Simranjit Kaur; Minakshi; Abhivyakti; Paramdeep Kaur; Sonal Singhal (Bioresource Technology, 2026)

Thermal signatures in breast cancer: Deciphering latent biomarkers through deep learning and explainable AI - Sachin Kansal; Simranjit Kaur; Arnav Jain; Somya Bansal; Mansi Gambhir (Journal of Thermal Biology, 2026)

Exploring rancidity in pearl millet flour: A lipidomic and biochemical approach - Rasika Rajendra Aher; Rupam Kumar Bhunia; Simranjit Kaur; Hemalatha Sanivarapu; Sudhakar Reddy Palakolanu; Victor Taleon; Kiran Kumar Sharma; S.K. Gupta; Govindaraj Mahalingam; Saikat Datta Mazumdar; Pooja Bhatnagar-Mathur (Journal of Cereal Science, 2025)

Importance of Gut Microbiota Dysbiosis and Circadian Disruption–Associated Biomarkers in Emergence of Alzheimer’s Disease - Simranjit Kaur; Deepali Kumari; Manoj P. Dandekar (Molecular Neurobiology, 2025)

Ursolic Acid and Caprylic Acid Cocktail Approach Against Pentylenetetrazole-induced Seizures-like Behavior in Adult Zebrafish: Preclinical Study - Deepali Sharma; Simranjeet Walia; Simranjit Kaur; Lakshay Kapil; Charan Singh; Arti Singh (Journal of Molecular Neuroscience, 2025)

Coenzyme Q10 ameliorates chemotherapy-induced cognitive impairment in mice: a preclinical study - Simranjit Kaur; Palak Ahuja; Lakshay Kapil; Deepali Sharma; Charan Singh; Arti Singh (Molecular Biology Reports, 2024)

Enhanced antichemobrain activity of amino acid assisted ferulic acid solid dispersion in adult zebrafish (Danio rerio) - Deeksha Shukla; Simranjit Kaur; Arti Singh; Raj Kumar Narang; Charan Singh (Drug Delivery and Translational Research, 2024)

Brain resident microglia in Alzheimer’s disease: foe or friends - Simranjit Kaur; Malleshwari K.; Anamika Sharma; Vijayasree V. Giridharan; Manoj P. Dandekar (Inflammopharmacology, 2024)

In-vitro and in-vivo studies of two-drug cocktail therapy targeting chemobrain via the Nrf2/NF-κB signaling pathway - Arti Singh; Vishal Kumar; Urvashi Langeh; Lakshay Kapil; Simranjit Kaur; Nitasha Rana; Arka Bhattacharya; Rajveer Singh; Jasvinder Singh Bhatti; Charan Singh (Journal of Molecular Histology, 2024)

Polymer-mediated nanoformulations: a promising strategy for cancer immunotherapy - Simranjit Kaur; Adesh K. Saini; Hardeep Singh Tuli; Nancy Garg; Hemant Joshi; Mehmet Varol; Jagjit Kaur; Anil K. Chhillar; Reena V. Saini (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Biotic and abiotic responses to soilborne pathogens and environmental predictors of soil health - Bruna D. Batista; Juntao Wang; Hongwei Liu; Simranjit Kaur; Catriona A. Macdonald; Zhiguang Qiu; Pankaj Trivedi; Manuel Delgado-Baquerizo; Chao Xiong; Jinsong Liang; Michael Bange; Brajesh K. Singh (Soil Biology and Biochemistry, 2024)

Response of the plant core microbiome to Fusarium oxysporum infection and identification of the pathobiome - Zhiguang Qiu; Jay Prakash Verma; Hongwei Liu; Juntao Wang; Bruna D. Batista; Simranjit Kaur; Arthur Prudêncio de Araujo Pereira; Catriona A. Macdonald; Pankaj Trivedi; Tim Weaver; Warren C. Conaty; David T. Tissue; et al. (Environmental Microbiology, 2022)
Plant core microbiomes consist of persistent key members that provide critical host functions, but their assemblages can be interrupted by biotic and abiotic stresses. The pathobiome is comprised of dynamic microbial interactions in response to disease status of the host. Hence, identifying variation in the core microbiome and pathobiome can significantly advance our understanding of microbial–microbial interactions and consequences for disease progression and host functions. In this study, we combined glasshouse and field studies to analyse the soil and plant rhizosphere microbiome of cotton plants ( Gossypium hirsutum ) in the presence of a cotton‐specific fungal pathogen, Fusarium oxysporum f. sp. vasinfectum (FOV). We found that FOV directly and consistently altered the rhizosphere microbiome, but the biocontrol agents enabled microbial assemblages to resist pathogenic stress. Using co‐occurrence network analysis of the core microbiome, we identified the pathobiome comprised of the pathogen and key associate phylotypes in the cotton microbiome. Isolation and application of some negatively correlated pathobiome members provided protection against plant infection. Importantly, our field survey from multiple cotton fields validated the pattern and responses of core microbiomes under FOV infection. This study advances key understanding of core microbiome responses and existence of plant pathobiomes, which provides a novel framework to better manage plant diseases in agriculture and natural settings.

Behavioural hormoligosis in oviposition preference of Bemisia tabaci (Gennadius) in Bt cotton - Simranjit Kaur; Vijay Kumar; Manjeet Kaur Sangha (International Journal of Tropical Insect Science, 2022)

Characterization of oleosin genes from forage sorghum in Arabidopsis and yeast reveals their role in storage lipid stability - Rabishankar Ojha; Simranjit Kaur; Kshitija Sinha; Kirti Chawla; Sumandeep Kaur; Harish Jadhav; Manmehar Kaur; Rupam Kumar Bhunia (Planta, 2021)

Microbial inoculants as plant growth stimulating and soil nutrient availability enhancing options for cucumber under protected cultivation - Kaur Simranjit; Amrita Kanchan; Radha Prasanna; Kunal Ranjan; Balasubramanian Ramakrishnan; Awani Kumar Singh; Yashbir Singh Shivay (World Journal of Microbiology and Biotechnology, 2019)

Exploring Crop–Microbiome Interactions Towards Improving Symbiotic Performance of Chickpea (Cicer arietinum) Cultivars Using Cyanobacterial Inoculants - Kaur Simranjit; Kunal Ranjan; Radha Prasanna; Balasubramanian Ramakrishnan; Amrita Kanchan; Yashbir Singh Shivay (Journal of Plant Growth Regulation, 2019)

Informing Environmental Water Management Decisions: Using Conditional Probability Networks to Address the Information Needs of Planning and Implementation Cycles - Avril C. Horne; Joanna M. Szemis; J. Angus Webb; Simranjit Kaur; Michael J. Stewardson; Nick Bond; Rory Nathan (Environmental Management, 2018)

Cyanobacterial and rhizobial inoculation modulates the plant physiological attributes and nodule microbial communities of chickpea - Radha Prasanna; Balasubramanian Ramakrishnan; Kaur Simranjit; Kunal Ranjan; Amrita Kanchan; Firoz Hossain; Lata Nain (Archives of Microbiology, 2017)

Microbial inoculation of seeds characteristically shapes the rhizosphere microbiome in desi and kabuli chickpea types - Balasubramanian Ramakrishnan; Simranjit Kaur; Radha Prasanna; Kunal Ranjan; Amrita Kanchan; Firoz Hossain; Yashbir Singh Shivay; Lata Nain (Journal of Soils and Sediments, 2017)

γ-Aminobutyric Acid (GABA) Imparts Partial Protection from Heat Stress Injury to Rice Seedlings by Improving Leaf Turgor and Upregulating Osmoprotectants and Antioxidants - Harsh Nayyar; Ramanpreet Kaur; Simranjit Kaur; R. Singh (Journal of Plant Growth Regulation, 2014)